THE IMPACT OF BANK GOVERNANCE IN LIGHT OF FINANCIAL AND ECONOMIC CRISES- AN APPLIED STUDY IN THE IRAQI MIDDLE EAST INVESTMENT BANK – BAGHDAD - Assistant Prof Jasim. M, Doai; Assistant Lecturer. Hanan Jumaa Hanzal (American Journals, 2024)
Government banking is receiving increasing attention from financial institutions in all countries due to its crucial role in avoiding the risks of financial and economic crises. In light of this, the research aims to measure governance variables in the face of these crises, as the Iraqi Middle East Investment Bank and the Bank of Baghdad tested a research model, and this was tested through two hypotheses, as several statistical methods were used, including descriptive statistics for the arithmetic mean and standard deviation. A set of conclusions were reached, including There is a clear interest on the part of the bank under discussion in applying the foundations, principles and standards of governance, as they are a guarantee characterized by transparency. Accordingly, recommendations were presented, including the importance of taking sound financial and administrative measures to confront financial and economic crises, including practicing basic activities in Work and avoiding activities (buying, selling, mortgage, etc.
Keywords: Governance, financial and economic crises.